1962
DOI: 10.1063/1.1777189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noncrystallizable Components on the Crystallization Kinetics of Polymers

Abstract: Articles you may be interested inEffect of high hydrostatic pressure on the dielectric relaxation in a non-crystallizable monohydroxy alcohol in its supercooled liquid and glassy statesThe effects of chain irregularities, treated as randomly introduced copolymeric units and of added monomeric diluents, on the nucleation rate of crystallizing polymeric systems have been calculated. A marked attenuation in the nucleation rate is expected under certain conditions as a consequence of the varying composition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…Although the changing features in the Raman spectra generally are associated with the difference in chain conformation, these same features may also be dependent on the difference in configurational disorder since a few defects along the chain can significantly influence the crystallization behavior. 27,28 The Raman shift region between 800 and 850 cm Ϫ1 corresponds primarily to the C-C stretching modes of the backbone; however, components of the CH, CH 2 , and CH 3 rocking modes can also contribute to the measured intensity. A previous study showed that the band at 812 cm Ϫ1 became a shoulder and overlapped with the band at 843 cm Ϫ1 upon melting, 29 indicating that iPP lost the regular ͑•••TGTG•••͒ conformational sequence, which in the crystals gave rise to a 3 1 helix.…”
Section: B Raman Resultsmentioning
confidence: 99%
“…Although the changing features in the Raman spectra generally are associated with the difference in chain conformation, these same features may also be dependent on the difference in configurational disorder since a few defects along the chain can significantly influence the crystallization behavior. 27,28 The Raman shift region between 800 and 850 cm Ϫ1 corresponds primarily to the C-C stretching modes of the backbone; however, components of the CH, CH 2 , and CH 3 rocking modes can also contribute to the measured intensity. A previous study showed that the band at 812 cm Ϫ1 became a shoulder and overlapped with the band at 843 cm Ϫ1 upon melting, 29 indicating that iPP lost the regular ͑•••TGTG•••͒ conformational sequence, which in the crystals gave rise to a 3 1 helix.…”
Section: B Raman Resultsmentioning
confidence: 99%
“…In general, the crystallization isotherms of copolymers deviate from the A vrami-type behavior, because the molten phase becomes enriched in the noncrystallizable component as crystallization progresses. 9 However, the experimental data for the copolyesters in this study satisfy the Avrami equation, and the Avrami exponents listed in Table II are almost close to 2, independent of crystallization temperature and copolymer composition. This means that the nucleation type and the crystal shape of the PBN homopolymer is similar to those of the copolyesters over the range of crystallization temperature investigated, and also that the isotherm shape does not change with the crystallization temperature.…”
Section: Res Ul Ts and Discussionmentioning
confidence: 99%
“…T/1/ (9) where L is the length of the substrate lamella. The criterion of the Z test for each regime is X = Kr for test of region I , Zs; 0.01 X = 2Kr for test of regime II , Z I (10) With eq 9, 10, and the known value of Kr obtained from the line slope, it is possible to estimate the range of L values and decide whether these L values are reasonable in each regime or not.…”
Section: ------------mentioning
confidence: 99%
“…16 -19 The addition of a noncrystallizable component significantly attenuates the nucleation rate, and the nucleation rate decreases with the conversion of crystallization. 20 In this study, the crystallization kinetics of PET and poly(ethylene terephthalate-co-isophthalate) (PETI) copolymers containing 2 and 12 mol % of isophthalate were investigated isothermally using DSC at large undercoolings (⌬T ϭ T m Ϫ T c ϭ 45ϳ90°C). The objectives of this study were to investigate the effect of poly(ethylene terephthalate-co-isophthalate (PEI) on the crystallization behavior of the copolyesters and to determine the molecular parameters governing the crystallization process of these copolyesters.…”
Section: Introductionmentioning
confidence: 99%